Decoupled versus coupled growth dynamics of an irregular eutectic alloy. (December 2020) - Mohagheghi, Samira; Bottin-Rousseau, Sabine; Akamatsu, Silvère; Şerefoğlu, Melis
Abstract: We present an experimental study of irregular growth patterns observed in real time during thin-sample directional solidification of a faceted/nonfaceted eutectic alloy, namely, the transparent 2-amino-2-methyl-1, 3-propanediol (AMPD)-succinonitrile (SCN) system. The body-centered cubic SCN crystals are nonfaceted, while monoclinic AMPD crystals grow as faceted needles. At low velocities (<0.3 µms −1 ), a decoupled growth regime is observed, during which the tip of the AMPD crystals grows ahead of the SCN-liquid interface. At intermediate velocities, an unsteady coupled-growth regime takes place, with intermittent pinning of triple SCN-AMPD-liquid junctions, and frequent noncrystallographic branching. At higher velocities (>1 µms −1 ), two-phase fingers form. Graphical abstract: Image, graphical abstract